Resposta :
Resposta:
segue resposta
Explicação passo a passo:
Seja a função f(x) = 2x
[tex]a) f(1) = 2.1 = 2[/tex]
[tex]b) f(4) = 2.4 = 8[/tex]
[tex]c) f(-1) = 2.(-1) = -2[/tex]
[tex]d) f(-2) = 2.(-2) = -4[/tex]
[tex]e) f(3) = 2.3 = 6[/tex]
[tex]f) f(0) = 2.0 = 0[/tex]
Resposta:
1) Dada a função f (x) = 2x, determine x para:
a) f (1) = 2x → f (1 ) = 2 * 1 → f(1) = 2
b) f (4) = 2x → f(4) = 2 * 4 → f(4) = 8
c) f (- 1) =2x → f(-1) = 2 * (-1) → f(-1) = -2
d) f (- 2) = 2x → f(-2) = 2 * (-2) → f(-2) = -4
e) f (3) = 2x → f(3) = 2 * 3 → f(3) = 6
f) f (0) = 2x → f(0) = 2*0 → f(0) = 0